(3GdbGehS GdeMjW hGdbCHhS GdhSjWs - (3eMeO Hf jYbhH Hf eMeO, eLO GdOjf GdajQhRGHGOj,J (B817 (3g` s
(3ChdgG (B:s
(3HGH GdMGA GdegedI , bdJ CHOdhgG ef GdYjf ai bhdge QjM HOd bhdge QjY hYcSg , bhdge UHY dZI ai UHM , hcdGgeG bdjd hdPdc de jPcQg GdLhgQi s
(3BNQgG (B:s
(3hGdMjQ jTHg GdMXjQI Ch GdMi heKdg GdeKd GdaQGA ChQOg (B[ (3h(B] (3GdejOGfi hZjQg , hgh bhdge (B: (3ef GYJeO Ydi MGQI EdN GfJgi GdLRA GdKGdK ef CYeGd CQHYI hjdjdg aUd GdNGA GdeYLeI s
(3GdLRA GdKGdK ef GdfSNI GdSGHbI faSgGs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B147s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs